The crystal structures, phase stabilities, electronic structures and bonding features of iridium borides from first-principles calculations. Issue 19 (14th April 2022) - Zhang, Jinquan; Jin, Yuanyuan; Zhang, Chuanzhao; Wang, Yanqi; Tang, Libiao; Li, Song; Ju, Meng; Wang, Jingjing; Sun, Weiguo; Dou, Xilong
Abstract : We mainly probe into phase stabilities, structural characters, elastic anisotropy and bonding features of the iridium borides under ambient pressure. Abstract : We present results of an unbiased structure search for the lowest energy crystalline structures of various stoichiometric iridium borides, using first-principles calculations combined with particle swarm optimization algorithms. As a result, besides three stable phases of C 2/ m -Ir3 B2, Fmm 2-Ir4 B3, and Cm -Ir4 B5, three promising metastable phases, namely, P 21 / m -Ir2 B, P 21 / m -IrB, and Pnma -Ir3 B4, whose energies are within 20 meV per atom above the convex hull curve, are also identified at ambient pressure. The high bulk modulus of 301 GPa, highest shear modulus of 148 GPa, and smallest Poisson's ratio of 0.29 for C 2/ m -Ir3 B2 make it a promising low compressible material. C 2/ m -Ir3 B2 is predicted to possess the highest Vickers hardnesses, with a Vickers hardness of 13.1 GPa and 19.4 GPa based on Chen's model and Mazhnik-Oganov's model respectively, and a high fracture toughness of 5.17 MPa m 0.5 . The anisotropic indexes and the three-dimensional surface constructions of Young's modulus indicate that Ir–B compounds are anisotropic with the sequence of the elastic anisotropy of Ir2 B > IrB > Ir4 B5 > Ir3 B4 > Ir4 B3 > Ir3 B2 . Remarkably, these iridium borides are all ductile. We further find that the four Ir–B phases of P 21 / m -Ir2 B, C 2/ m -Ir3 B2, P 21 / m -IrB, and Fmm 2-Ir4 B3 possess dominant Ir–B covalent bonding character, while strong B–B and Ir–B covalent bonds are present in Cm -Ir4 B5 and Pnma -Ir3 B4, which are responsible for their excellent mechanical properties.